Penggunaan Teknologi dalam Membantu Peserta Didik Sekolah Dasar dengan Kesulitan Membaca : Literature Review - Febrina Damayanti; Dina Rahayu; Adrias Adrias; Salmaini Safitri Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Reading ability is an important basic skill for elementary school student. However, not all students can master it well due to various factors, such as delayed language development, lack of stimulus, and specific learning disorders such as dyslexia.This research aims to determine Ultilization impact technology in supporting reading literacy for students with reading difficulties. The method employed is a literature review by analyzing many previous studies Associated with the utlization of technology in improving reading skills.the findings of the study show that digital-based digital innovation , such as interactive learning applications, Text-to-Speech (TTS), Augmented Reality (AR), and QR-Code technology,can improve students’ reading skills. The main obstacles in implementing technologies that are less relevant to learning. Recommendations provided include increasing technology, and integrating digital methods with conventional learning approaches. This research is expected to be a reference for educators and stakeholders in the developing process more effective strategies to improve elementary school students’ reading skills by optimally utilizing technology.